2022
DOI: 10.1038/s41598-022-23611-0
|View full text |Cite
|
Sign up to set email alerts
|

Competition between electrostatic interactions and halogen bonding in the protein–ligand system: structural and thermodynamic studies of 5,6-dibromobenzotriazole-hCK2α complexes

Abstract: CK2 is a member of the CMGC group of eukaryotic protein kinases and a cancer drug target. It can be efficiently inhibited by halogenated benzotriazoles and benzimidazoles. Depending on the scaffold, substitution pattern, and pH, these compounds are either neutral or anionic. Their binding poses are dictated by a hydrophobic effect (desolvation) and a tug of war between a salt bridge/hydrogen bond (to K68) and halogen bonding (to E114 and V116 backbone oxygens). Here, we test the idea that binding poses might b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(17 citation statements)
references
References 78 publications
1
16
0
Order By: Relevance
“…However, a slight opposite trend was observed for TBBt binding, for which anionic form predominates at all tested pH. We had assigned this apparent variation in TBBt binding by WT protein to the pH-induced (de)protonation of the neighboring histidine residue (putatively His160, with a theoretical pK a of ~ 7) 18 . To confirm this hypothesis, we analyzed a series of DSF data collected at different pH for both histidine mutants against the values previously reported for the WT protein (Table 4 and Fig.…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…However, a slight opposite trend was observed for TBBt binding, for which anionic form predominates at all tested pH. We had assigned this apparent variation in TBBt binding by WT protein to the pH-induced (de)protonation of the neighboring histidine residue (putatively His160, with a theoretical pK a of ~ 7) 18 . To confirm this hypothesis, we analyzed a series of DSF data collected at different pH for both histidine mutants against the values previously reported for the WT protein (Table 4 and Fig.…”
Section: Resultsmentioning
confidence: 93%
“…Our recent study demonstrated that pH-dependent binding of 5,6-Br 2 Bt is due to forced ligand deprotonation upon the binding event 18 . However, a slight opposite trend was observed for TBBt binding, for which anionic form predominates at all tested pH.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations